1998
DOI: 10.1002/(sici)1099-1085(199807)12:9<1461::aid-hyp650>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The composition of nutrient fluxes from contrasting UK river basins

Abstract: Abstract:Accurate estimates of N and P loads were obtained for four contrasting UK river basins over a complete annual cycle. The fractionation of these loads into dissolved and particulate, and inorganic and organic components allowed a detailed examination of the nutrient load composition and of the factors in¯uencing both the relative and absolute magnitude of these components. The particulate phosphorus (TPP) loads account for 26±75% of the annual total phosphorus (TP) transport and are predominantly inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…It was also much lower than values for the similar-sized River Dart catchment in the UK (186 kg km" 2 yr" 1 ), which is almost all in permanent pasture (Russell et al 1998), and for other values reported by Goulding et al (1996) for heavily fertilised plots in the UK (up to 300^00 kg km" 2 yr 1 ). During the storm, discharge rose and receded very rapidly (Fig.…”
Section: Temporal Variability Of Tpcontrasting
confidence: 50%
See 2 more Smart Citations
“…It was also much lower than values for the similar-sized River Dart catchment in the UK (186 kg km" 2 yr" 1 ), which is almost all in permanent pasture (Russell et al 1998), and for other values reported by Goulding et al (1996) for heavily fertilised plots in the UK (up to 300^00 kg km" 2 yr 1 ). During the storm, discharge rose and receded very rapidly (Fig.…”
Section: Temporal Variability Of Tpcontrasting
confidence: 50%
“…Boxplots were constructed for concentrations at each station. The proportion of DRP to TP can be used to evaluate the amount of P bound to solids and sources and effects of P (Dils & Heathwaite 1996;Haygarth et al 1998;Russell et al 1998). Thus, the proportion of DRP to TP was estimated for each station.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies assessing the impact of catchment-scale factors on stream fish assemblages revealed that agriculture and deforestation influence the structure of fish habitat by providing sediments to streams (Russell et al, 1998;Huryn et al, 2002;Quinn and Stroud, 2002). In the present study, the amount of unforested area in a catchment was shown to influence fish species composition.…”
Section: Relative Importance Of the Catchment And Site Scale Factorssupporting
confidence: 46%
“…However, area-weighted TP fluxes for the Wye are also lower than corresponding TP yields for other lowland UK rivers of similar catchment scale (e.g. 1.6 -2.1 kg-P ha -1 a -1 , Russell et al, 1998). For the Wye, TP loads may be underestimated as a result of the relative infrequency of water sampling (monthly intervals), which has poor coverage of high-flow periods, when peak TP is transported.…”
Section: Nutrient Loads and Source Contributionsmentioning
confidence: 84%